Late Steps in Secretory Lysosome Exocytosis in Cytotoxic Lymphocytes - van der Sluijs, Peter; Zibouche, Mallik; van Kerkhof, Peter (Frontiers in Immunology, 2013)
Natural Killer cells are a subset of cytototoxic lymphocytes that are important in host defense against infections and transformed cells. They exert this function through recognition of target cells by cell surface receptors, which triggers a signaling program that results in a re-orientation of the microtubule oranizing center and secretory lysosomes towards the target cell. Upon movement of secretory lysosomes to the plasma membrane and subsequent fusion, toxic proteins are released by secretory lysomes in the immunological synapse which then enter and kill the target cell. In this minireview we highlight recent progress in our knowledge of late steps in this specialized secretion pathway and address important open questions.